Comparing and contrasting student identity change in different educational settings - Zhu, Dandan (2016)
This thesis explores the nature and change of student identity in two universities with different educational settings in China. The thesis also focuses on whether and how two different institutional contexts influence university students’ identity change. The universities in the study are Zhejiang University, which is a Chinese university, and the university of Nottingham Ningbo China, a transnational university (British university campus) in China. The theoretical framework of the study draws from sociological and social psychological theories of identities, and in particular Burke and Set’s (2009) identity theory. Burke and Stets’ (2009) model proposed three dimensions when analysing identities: role identity, group identity and personal identity. This study uses this model to investigate students’ identity change in the afore-mentioned universities.